Changes in physicochemical attributes of sweet pepper (Capsicum annum L.) during fruit growth and development (Bangladesh Journal of Agricultural Research, 2014)
Changes in physicochemical attributes of sweet pepper var. BARI Misti Morich-1 during fruit growth and development were studied. Capsicum flowers were tagged on the day of anthesis and fruits were harvested at three days interval started on 33 days after anthesis (DAA) until 48 DAA, when turned to light green colour. Length, diameter, and weight of fruits were linearly increased from 33 DAA to 48 DAA. Dry matter content, TSS, firmness, and shelf life of fruits were also gradually increased with lengthen the harvesting time from flower anthesis and reached from 5.1 to 7.3%, 4 to 5%, 7.1 to 14.5 kgf cm-2 and 9.6 days to 21.3 days, respectively, from 33 DAA to 48 DAA. However, ascorbic acid content of fruits was sharply decreased from 68 to 56 mg/100g from first harvest to last harvest, respectively. Hue angle declined with time while chroma and lightness values increased with fruit maturity. Considering all physical and nutritional characteristics and shelf life along with sensory evaluation scores, fruits of BARI Misti Morich-1 was found suitable to harvest after 45 days of anthesis, when they attained length 12.2 cm, diameter 8.8 cm, and weight 191g. Moreover, fruits were crispier, glossy with attractive colour and flavour and contained 58 mg/100g ascorbic acid at this maturity stage. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20446 Bangladesh J. Agril. Res. 39(2): 373-383, June 2014